Integrating artificial intelligence in higher education: perceptions, challenges, and strategies for academic innovation - Dusana Alshatti Schmidt; Bedour Alboloushi; Anisha Thomas; Rodrigo Magalhaes (Computers and Education Open)
In recent years artificial intelligence (AI) has emerged as a transformative force across various industries impacting the workforce dynamics. To ensure that graduates possess the necessary skills, higher education institutions are exploring new ways to align their approaches with labor market demands. This study examines how AI is being integrated in higher education institutions, aimed at gaining an understanding of how students and faculty perceive AI, how it is applied, its impact on performance, the challenges encountered, and the strategies used for its adoption. The study also aims to provide practical, evidence-based recommendations for effective integration of AI into curriculum. The research employs a qualitative approach, incorporating focus group interviews and open-ended questionnaires. Findings indicate that while both faculty and students recognize AI's transformative potential and benefits, they are also concerned about its impact on critical thinking and academic integrity. Faculty use AI tools for teaching and assessment, but face challenges with tool accuracy and integration. Students utilize AI for academic tasks but struggle with reliability and ethical issues. The study highlights the need for increased awareness, continuous professional development, and ethical guidelines to overcome these challenges. The findings of this study contribute to the successful adoption of AI in higher education in general, ensuring that both teaching and learning processes are enriched by the potential of AI.